Surgery for Young Adults With Aortic Valve Disease not Amenable to Repair - Zakkar, Mustafa; Bruno, Vito Domanico; Visan, Alexandru Ciprian; Curtis, Stephanie; Angelini, Gianni; Lansac, Emmanuel; Stoica, Serban (Frontiers in Surgery, 2018)
Aortic valve replacement is the gold standard for the management of patients with severe aortic stenosis or mixed pathology that is not amenable to repair according to currently available guidelines. Such a simplified approach may be suitable for many patients, but it is far from ideal for young adults considering emerging evidence demonstrating that conventional valve replacement in this cohort of patients is associated with inferior long-term survival when compared to the general population. Moreover; the utilisation of mechanical and bioprosthetic valves can significantly impact on quality and is linked to increased rates of morbidities. Other available options such as stentless valve, homografts, valve reconstruction and Ross operation can be an appealing alternative to conventional valve replacement. Young patients should be fully informed about all the options available - shared decision making is now part of modern informed consent. This can be achieved when referring physicians have a better understanding of the short and long term outcomes associated with every intervention, in terms of survival and quality of life. This review presents up to date evidence for available surgical options for young adults with aortic stenosis and mixed disease not amenable to repair.